Farmer participatory roles in technology Development and transfer: A case study from on-farm vertisol technology experience in Ethiopia - Asamenew, G.; Mohamed-Saleem, M.A. (FARM Africa, 1992)
Describes farmers' participatory roles in technology Development and transfer, drawing on experience from on-farm Vertisol technology research in Ethiopia, i.e. constant consultation w. farmers enabled technical refinements and brought attitudinal changes to the technology by using on animal drawn broad-bed maker (BBM) for shaping land structures to overcome seasonal waterlogging problem, and this opens up opportunities for alternative land uses such as early planting of improved seed to multiple cropping which showed increased crop yields, income, land and labour productivity, and the potential impact of the technology seems high judging farmers' interest in its transfer to other farmers.